Calculation of Average Global Accessibility Conditions for Bicycles Considering the Longitudinal Road Slope: Case Study Ibagué – Colombia (2024)
Territorial accessibility conditions are a relevant concept for the continuous development of cities; hence, it is necessary to accurately determine their characteristics and how population or physical factors influence them when interacting with transportation. In the present study, a mathematical model is developed using transport supply models to evaluate the average global accessibility of bicycle infrastructure, considering factors such as the longitudinal slope of the road and the socioeconomic stratum. The methodology focuses on six main stages: starting with the collection of population census data and GPX traces of trips made in the mode; second, analyzing the relationship between slope and speed using linear regressions for different categories of roads with data from the previous stage; third, conditioning geographic information layers with and without slope; fourth, evaluating geographic accessibility using Dijkstra’s shortest path algorithm; fifth, calculating the average global accessibility and generating isochronous curve maps using the ordinary Kriging geostatistical algorithm; sixth, estimating the relationship between travel times considering the slope of the road and a base scenario without slope. The results indicate that steeper slopes significantly reduce the average speed of cyclists, which in turn increases travel times and negatively affects accessibility conditions. Additionally, it shows how topographical features, and the city sector influence the mobility of the cycling community. These findings reveal the importance of considering road slope in urban planning to generate strategies that develop efficient road infrastructure and promote the use of bicycles as a means of transport, fostering sustainable mobility.